Noise levels during the milking of dairies with mechanical systems in the highlands of the tropics of Colombia and its effect on milk quality and animal welfare - García, Fredy Enrique (2019)
The objective of this study was to determine the noise levels during milking inmechanical milking systems (fixed and mobile) and their relationship with animal welfareand milk quality. The noise levels were measured in eight farms located in the municipalitiesof La Sabana de Bogotá (Colombia). The exposure of cows to noise was measured in themilking parlour (RUME), in the milking parlour before the milking (RUIN) and at the endof milking, with the equipment turned off (RUFI). Milking was also classified according to the noise level as noisy milking and milking with tolerable noise. The groups were comparedin relation to the production, composition and quality of milk, as well as behavior associatedwith stress. Significant differences were found for the somatic cell count and the numberof mesophilic bacteria (p<0.05), being higher in the so-called noisy milking.